The Image of the "Chair" in the Creative Life of Gevorg Mshetsi Javrushyan - Lilit Arsenyan (Journal of Architectural and Engineering Research)
In this research we have studied the pictorial features of "chair" as a main character and the semantic content of the image in painter, sculptor and designer Gevorg Mshetsi Javrushyan`s three-dimentional, volumetric series of works named "Chairs". These unique collages created over different years predominate in his creative life (they are approximately 60), so they have a great role and importance in the context of studying and enlightening his art. Having a unique ideological and philosophical content, an interesting presentation of external form, they have received various interpretations. Each "Chair" has something to say, some message, which can be understood through the title mainly presented in the form of catchprase or aphorism. The article refers to the depiction of the chair in the world and Armenian fine art, starting from its initial stage of the growth of importance. Through individual examples, comparative parallels are drawn between the similar works of the artist and those of other artists representing different artistic movements and cultural periods. Thus, this article aims to study this period of Gevorg Mshetsi’s work, to present and illuminate it for art lovers and the scientific community, and, importantly, to do so in the context of Armenian and world fine art.